(untitled) (JED (Jurnal Etika Demokrasi), 2021)
Abstract. This article aims to describe the implementation of the character building program through mentoring activities at SMP Negeri 1 Solok Selatan. This article uses a qualitative descriptive approach with the research subjects consisting of the vice principal of student affairs, mentoring coaches, mentoring administrators, mentors, and mentoring participants. The results of this study indicate that: 1) The mentoring program at SMP Negeri 1 Solok Selatan is carried out with two activities, namely the main activity which is routine every Saturday, and complementary activities for mentoring participants, mentors, and the mentoring management team; 2) There are seven basic character forms produced after participating in mentoring activities at SMP Negeri 1 Solok Selatan. First, increasing the correct understanding of Islam according to the Al Quran and Sunnah. Second, the close brotherhood between mentoring students. Third, the students’ ability to advise each other. Fourth, increasing student achievement in the religious, academic and non-academic fields. Fifth, the implementation of congregational worship at the mosque. Sixth, the improvement of students’ abilities in reading the Al Quran. Seventh, the realization of good interactions between students and teachers, students and staff, and students and students. Keywords: Character Development; Mentoring Activities; Descriptive Research Abstrak. Artikel ini bertujuan untuk mendeskripsikan pelaksanaan program pembinaan karakter melalui kegiatan mentoring di SMP Negeri 1 Solok Selatan. Artikel ini menggunakan pendekatan deskriptif kualitatif dengan subjek penelitian terdiri dari wakil kepala sekolah bagian kesiswaan, pembina mentoring, pengurus mentoring, mentor, dan peserta mentoring. Hasil penelitian ini menunjukkan bahwa: 1) Pelaksanaan program mentoring di SMP Negeri 1 Solok Selatan dilaksanakan dengan dua kegiatan yakni kegiatan utama yang secara rutin setiap hari Sabtu, dan kegiatan pelengkap untuk peserta mentoring, mentor, dan tim pengelola mentoring; 2) Terdapat tujuh bentuk karakter dasar yang dihasilkan setelah mengikuti kegiatan mentoring di SMP Negeri 1 Solok Selatan. Pertama, bertambahnya pemahaman Islam yang benar sesuai dengan Al Quran dan Sunnah. Kedua, eratnya persaudaraan antar siswa mentoring. Ketiga, kemampuan siswa dalam saling menasehati. Keempat, meningkatnya prestasi siswa baik bidang keagamaan, akademik, maupun non akademik. Kelima, pelaksanaan ibadah secara berjamaah di masjid. Keenam, peningkatan kemampuan siswa dalam membaca Al Quran. Ketujuh, terwujudnya interaksi yang baik antara siswa dengan guru, siswa dengan staf, dan siswa dengan siswa. Kata Kunci: Pembinaan Karakter, Siswa, Mentoring